Development and sensory experience dependent regulation of microglia in barrel cortex. Issue 4 (18th October 2019) - Kalambogias, John; Chen, Chia‐Chien; Khan, Safraz; Son, Titus; Wercberger, Racheli; Headlam, Carolyn; Lin, Cindy; Brumberg, Joshua C.
Abstract: The barrel cortex is within the primary somatosensory cortex of the rodent, and processes signals from the vibrissae. Much focus has been devoted to the function of neurons, more recently, the role of glial cells in the processing of sensory input has gained increasing interest. Microglia are the principal immune cells of the nervous system that survey and regulate the cellular constituents of the dynamic nervous system. We investigated the normal and disrupted development of microglia in barrel cortex by chronically depriving sensory signals via whisker trimming for the animals' first postnatal month. Using immunohistochemistry to label microglia, we performed morphological reconstructions as well as densitometry analyses as a function of developmental age and sensory experience. Findings suggest that both developmental age and sensory experience has profound impact on microglia morphology. Following chronic sensory deprivation, microglia undergo a morphological transition from a monitoring or resting state to an altered morphological state, by exhibiting expanded cell body size and retracted processes. Sensory restoration via whisker regrowth returns these morphological alterations back to age‐matched control values. Our results indicate that microglia may be recruited to participate in the modulation of neuronal structural remodeling during developmental critical periods and in response to alteration in sensory input. Abstract : Mice were either reared with intact whiskers or unilaterally trimmed for the first postnatal month. Subsequent evaluation of microglia within their barrel cortex revealed that peripheral whisker trimming results in enlarged microglia somata and retraction of their processes. These results suggest that peripheral sensory input can shape microglial responses within the mouse barrel cortex. Scale bar represents 10 μm.